Nepal - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Nepal’s risk of external debt distress remains low. Under the revised IMF/World Bank Debt Sustainability Analysis Framework for Low Income Countries (LIC-DSF), all debt and debt service ratios are projected to remain below relevant indicative threshold values. Following a prolonged decline, to 25 percent of GDP in mid-2015, the sum of external and domestic public debt rose to 30 percent of GDP in mid-2018. A further rise in total public debt is projected, to about 35 percent of GDP in the medium term and about 48 percent of GDP in the long term, owing to continuing fiscal and current account deficits, as the authorities implement fiscal federalism and aim to put the economy on a higher growth path. Stress tests suggest that debt burden indicators are vulnerable to growth/exports shocks and natural disasters. This underscores the importance of implementing sound macro-economic policies. Efforts to improve the business climate and competitiveness through high-quality public investment and structural reforms would support growth and expand foreign exchange income streams.